ANALISIS DEGRADASI KETAHANAN KOROSI INTEGRITAS PANEL BODY ELECTRIC SHUTTLE BUS 14 SEATS MENGGUNAKAN ACCELERATED SALT SPRAY TESTER - Raden Muhamad Dany Husni; Yusep Sukrawan; Sriyono (Badan Penerbit Universitas Muria Kudus, 2026)
This study aims to analyze the degradation rate of corrosion resistance in the body panel materials of a 14-seat electric shuttle bus. In line with the Indonesian government's 2030 target to achieve 2 million electric cars and 13 million electric motorcycles, the durability of commercial electric vehicle components such as shuttle buses is highly crucial. Testing was conducted using the Accelerated Salt Spray Tester method, referring to the ASTM B117 standard, to simulate extreme corrosive environmental exposure in a short period. Body panel specimens were tested in a salt fog chamber with strictly controlled parameters, including NaCl solution concentration and chamber temperature. Material integrity evaluation was performed by comparing the condition of specimens before and after testing, including mass loss rate, visual observation of corrosion product formation, and pitting indications. The results of this study are expected to provide technical recommendations regarding optimal material selection and coating systems to enhance the service life of commercial electric vehicles in Indonesia's tropical climate.